On-chip supercontinuum generation in nanostructured Ge11.5As24Se64.5 chalcogenide waveguides using Panda-ring resonator - S. Suwanarat (Results in Physics, 2018)
The on-chip scale microring circuit is proposed to numerically investigate the supercontinuum (SC) generation of light power. The device is formed by the chalcogenide Panda-ring resonator with the nanoscale planar waveguide using Ge11.5As24Se64.5 chalcogenide glass channel waveguide, air-clad and MgF2 glass for lower cladding. The waveguide is designed to exhibit normal dispersion along with a low-energy pumped at 1.55 μm using a short pulse, which has the duration of 50 fs and peak power ranging from 1 W to 100 W. The numerical result obtained has shown a good-quality SC generation of both the spectral bandwidth and high output peak power. All SC spectral extended to more than 13 μm by cumulative Kerr nonlinearities. The obtained results can be useful for developing new experimental work in the important area of SC generation on compact chip broadband sources, which can be used in both infrared and radio wave applications. Keywords: Supercontinuum, Panda-ring resonator, Cumulative nonlinearities, Chalcogenide waveguide, ChG, Split-step fouriermethod (SSFM), Generalized nonlinear Schrodinger equation (GNLS), Group-velocity dispersion (GVD)